Experimental Investigation on the Mechanical and Microstructural Properties of Concrete with Agro-Waste - Godwin I, Antony; Deborah S, Nancy; Ponraj I, Julius; Blessho R, Vinslin; C, Stephen (International Journal of Engineering and Technology, 2018)
Due to ever-increasing disposal problems of agricultural wastes in developing countries have created opportunities for use of agricultural wastes in the construction industries. An attempt has been carried out by partial replacement of cement with areca-nut shell, fine aggregate with coconut shell powder by pulverizing it into ashes and coarse aggregate with oil palm shell9. Concrete specimens were cast and cured for 28 days, a detailed comparison is made with conventional concrete and concrete with agrowaste by testing the specimens to finding the mechanical and durability properties like compressive, tensile flexural and rapid chloride penetration test. From the experimental results, it is found that the combination comprising of 10% of areca nut ash (ASA), 5% of coconut shell charcoal powder (CSCP) and 5% of oil palm shell (OPS) shows desirable results in enhancing the properties of agro waste concrete. The detailedmicrostructural investigation has been done to find the reason for enhancing the mechanical properties of concrete with agro waste by using the Scanning Electron Microscope(SEM), Energy-dispersive X-ray spectroscopy(EDAX) and X-ray diffraction(XRD) methods.Due to the presence of CSH gel and Ca(OH)2in concrete with agro waste specimens which attributes the strength and other properties.Â Â